2010
DOI: 10.4171/ifb/224
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and secondary bifurcation of heavy periodic hydroelastic travelling waves

Abstract: The existence question for two-dimensional symmetric steady waves travelling on the surface of a deep ocean beneath a heavy elastic membrane is analyzed as a problem in bifurcation theory. The behaviour of the two-dimensional cross-section of the membrane is modelled as a thin (unshearable), heavy, hyperelastic extensible rod, and the fluid beneath is supposed to be in steady two-dimensional irrotational motion under gravity. When the wavelength has been normalized to be 2π , and when gravity and the density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…The first part of the proof is analogous to that of [9, Theorem 4.8] (see also [1]). The second part involves calculating the determinant of 3 × 3-matrix, the entries of which depend transcendentally on the parameters of the problem.…”
Section: The Lyapunov-schmidt Reduction and Existence Of Trimodal Stementioning
confidence: 88%
“…The first part of the proof is analogous to that of [9, Theorem 4.8] (see also [1]). The second part involves calculating the determinant of 3 × 3-matrix, the entries of which depend transcendentally on the parameters of the problem.…”
Section: The Lyapunov-schmidt Reduction and Existence Of Trimodal Stementioning
confidence: 88%
“…Our approach is based on the Lyapunov-Schmidt reduction and the implicit function theorem. The same method was recently used to study the bifurcation of steady irrotational water waves under a heavy elastic membrane [1].…”
mentioning
confidence: 99%
“…Even if (θ, γ; c) yield a traveling wave solution (z, γ), we cannot expect that 2π-periodic θ to yield periodic z via (18). We would like for any 2π-periodic (θ, γ) that solve some equations analogous to (16) and (17) to correspond directly to a periodic traveling wave solution (z, γ) of (2), (5), and (10). Hence, in a manner closely analogous to [9], we modify the mappings in (16) and (17) to ensure this.…”
Section: 2mentioning
confidence: 99%
“…The second author, Siegel, and Liu have shown that the initial value problems for these Cosserat-type hydroelastic waves are well-posed in Sobolev spaces [8], [16]. Toland and Baldi and Toland have proved existence of periodic traveling hydroelastic water waves with and without mass including studying secondary bifurcations [25], [26], [10], [11]. A number of authors have also computed traveling hydroelastic water waves, finding results in 2D and 3D, computations of periodic and solitary waves, comparison with weakly nonlinear models, and comparison across different modelling assumptions for the bending force [13], [14], [17], [18], [19], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation